PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DENGAN KEPEMILIKAN MANAJERIAL SEBAGAI VARIABEL MODERATING - Hanni Chyntia Maita Putri; Surya Raharja (Diponegoro Journal of Accounting, 2013)
This research aims to analyze the influence of Corporate Social Responsibility to firm value and the influence of managerial ownership as the moderating variable in the relation between Corporate Social Responsibility and firm value. Corporate Social Responsibility is measured by the Corporate Social Responsibility Disclosure’s index and the firm value is represented by the Tobin’s Q ratio while managerial ownership is measured using the dummy variable.The sample of this research is the companies categorized in high profile industry listed in Indonesia Stock Exchange for the year of 2010 and 2011. Data collected by purposive sampling method. There are 67 companies in 2010 and 49 companies in 2011 fulfilled the requirement as the research’s sample. A total of 116 samples in this research analyzed using the multiple regression method The results show that Corporate Social Responsibility and managerial ownership simultaneously has positive and significant effect to the firm value. Corporate Social Responsibility also partially has positive and significant effect to the firm value. Finally, the managerial ownership also has an effect as moderating variable that strengthen relationship between Corporate Social Responsibility and firm value.